OPTIMALISASI PEMANFAATAN PANGAN LOKAL MELALUI PROSIGA DI DESA KARANG MULYA, LUBAI ULU, MUARA ENIM - Graciela Angelica Sianipar; Mahfuzhoh Fadillah Heryanda; Akintan Vatika; Ananda Aulia; Anastasya Priscilla; Bayu Satria; Fyrdha Aulya; Adelia Kesuma; Nurmalina Heliza; Savira Putri; Sy. Jihan Fadiyah; Tsabitah Fakhriyyah; Zaskia Amirarosa (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2026)
Health problems due to suboptimal food security are a crucial issue in Indonesia. Data on the prevalence of wasting toddlers in Muara Enim Regency is 5.4%. The implementation of community empowerment activities through education and demonstration of the Provision of Additional Food (PMT) made from local food is a strategic step in overcoming the problem of toddler nutrition while increasing family food security. The purpose of this activity is to encourage more creativity and independence in providing nutritious intake, so that it can contribute to reducing malnutrition rates and creating good family food security. The methods used in this activity are pretest and posttest, nutrition education is continued with a demonstration of cooking PMT cassava balls with 2 flavor variants, namely chocolate and egg fillings. The results of this activity showed an increase in respondents' knowledge regarding PMT from 56.25% to 93.75%. In the organoleptic test for taste parameters, the egg variant (P2) received 17% and the chocolate variant (P1) slightly higher at 18%, indicating that the sweet taste of chocolate is slightly preferred by toddlers. For the aroma parameter, the chocolate-filled cassava balls (P1) were higher at 17% compared to the egg variant (P2) with 16%, and the aftertaste of the egg variant (P2) scored 17%, slightly higher than the chocolate (P1) which received 16%. This activity provided direct experience for housewives in processing local food into nutritious food for children. Learning that involves practice will be easier to understand than only delivering material in theory.